Ultra-Pulsed CO2 Laser Osteotomy: A New Method for the Bone Preparation of Total Knee Arthroplasty - Ran, Tianfei; Lin, Chuanchuan; Ma, Tianying; Qin, Yinyin; Li, Jie; Zhang, Yuan; Xu, Yuan; Li, Changqing; Wang, Min (Frontiers in Bioengineering and Biotechnology, 2022)
Cementless total knee arthroplasty (TKA) can achieve long-term biological fixation but its application is limited by the risk of early aseptic loosening. One of the important reasons for early aseptic loosening is mechanical osteotomy tools can not achieve ideal bone preparation, because of their poor accuracy and serious bone tissue damage. Therefore, we designed the ultra-pulsed CO2 laser osteotomy system to solve these problems. To reveal the safety at tissue and cell levels of ultra-pulsed CO2 laser osteotomy system, a series of experiments on distal femur osteotomy in animals were performed. Then the bone surface characteristics were analyzed through scanning electron microscopy, and the bone thermal, mechanical damage were evaluated by histological analysis. Finally, MSCs were inoculated on the bone surfaces prepared by the two osteotomy tools, and the effect of cell adhesion was analyzed through a confocal laser scanning microscope (CLSM). We successfully achieved the TKA bone preparation of animal knees with the ultra-pulsed CO2 laser osteotomy system. Moreover, the biological evaluation results indicated that, compared with the traditional mechanical saw, the laser can preserve natural bone structure and cause no thermal damage to the bone. In addition, CLSM examination results showed that the laser-cut bone surface was more conducive to cell adhesion and infiltration than that cut by mechanical saw. Overall, these results indicate that ultra-pulsed pulsed CO2 laser can achieve non-invasive bone cutting, which may lead a new option for TKA bone preparation.